Real‐world application of a fast stool DNA test for colorectal cancer screening in primary screening positive population. (5th December 2022) - Zhu, Yunfeng; Zhao, Guodong; Ma, Weihua; Chen, Xinmin; Chen, Xiaofei; Li, Danning; Zhao, Shuyan; Xiong, Shangmin; Zheng, Minxue
Abstract: Background: Stool DNA test has been emerged as an effective noninvasive method for colorectal cancer (CRC) screening, but the real‐world performance of stool DNA test in Chinese population has rarely been reported. Methods: A total of 36, 527 subjects were recruited in Haining City from January 2021 to December 2021. Participants underwent primary screening by taking both two‐samples fecal immunochemical tests (FITs) and high‐risk factor questionnaire (HRFQ), and those who tested either positive by FITs or evaluated to be high risk by HRFQ were recommended to undertake subsequent stool DNA test and colonoscopy. Results: Of 36, 527 participants, 34, 778 (95%) completed both HRFQ and FITs, 9947 (29%) showed positive results during primary screening, and the colonoscopy compliance rate was 49%. Of primary screening positives, 8733 (88%) completed stool sample collections, and colonoscopy results from 4293 eligible participants were used for analyzing the performance of stool DNA test. The sensitivities for detecting CRC and advanced adenomas (AA) were 100% (95% CI: 60–100%) and 40% (95% CI: 34–46%), and the area under curve (AUC) was 0.961 (95% CI:0.954–0.967) and 0.625 (95% CI: 0.609–0.641), respectively. The specificity of stool DNA test was 84% (95% CI: 82–85%). The false‐positive rate for stool DNA test is about 10% less than that of primary screening. Conclusion: Stool DNA test is a cost‐effective and promising alternative strategy for CRC screening in China. Abstract : This study analyzed the performance of a new stool DNA test in a real‐world application for CRC screening in Chinese population, and indicated stool DNA test is a cost‐effective and promising alternative strategy for CRC screening in China.